Global Development Finance 2007 : The Globalization of Corporate Finance in Developing Countries, Volume 1. Review, Analysis, and Outlook - World Bank (2012)
The globalization of corporate finance also points to other challenges. As emerging-market corporations have expanded their international operations, they have increased their exposure to interest rate and currency risks. Concerns are growing that several countries in emerging Europe and Central Asia are experiencing a credit boom engendered by cross-border borrowing by banks of untested financial health and stamina. Some of these banks have increased their foreign exchange exposure to worrisome levels, a concern that warrants special attention from national policymakers. Given banks' critical role in domestic monetary systems, policymakers should step up their regulation of foreign borrowing by banks. The projected slowdown in global growth and tighter monetary policy in high-income countries are expected to make financing conditions for developing countries somewhat less favorable in coming years. While a soft landing is the most likely outcome, there are risks. Global development finance is the World Bank's annual review of global financial conditions facing developing countries. The current volume provides analysis of key trends and prospects, including coverage of capital raised by developing country based corporations.